Gender Disparities in the Science, Technology, Engineering, and Mathematics (STEM) Pipeline in Gandaki Province, Nepal: Enrolment and Faculty Representation - KC, Aarati; Hamal, Sharadha; Sharma, Bimala; Pokharel, Prayan; Bhandari, Dhaka Ram (Journal of Agriculture and Forestry University, 2026)
Women remain underrepresented in science, technology, engineering, and mathematics (STEM) education and careers, yet province-level evidence in Nepal is limited. This study examines women’s participation in STEM in Gandaki Province and explores the barriers influencing their entry, retention, and progression. An explanatory sequential mixed-methods design was employed, combining institutional data from 20 STEM academic institutions with purposively selected key informant interviews (n = 10) involving experienced STEM faculty. Quantitative findings indicate substantial variation in female participation across disciplines, with higher representation in health-related fields and lower representation in technical and field-based disciplines. Qualitative findings reveal that, despite increasing enrolment, women continue to face structural barriers, including financial and geographic constraints, gender stereotypes, workplace bias, and the dual burden of professional and household responsibilities. These factors limit not only entry into STEM fields but also long-term retention and career progression. These findings highlight persistent discipline-specific inequalities and underscore the need for targeted, gender-responsive interventions that support not only access but also retention and advancement of women across the STEM pipeline.